2013
DOI: 10.1155/2013/213109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of International Normalized Ratio Measurement between CoaguChek XS Plus and STA-R Coagulation Analyzers

Abstract: Background. Point-of-care testing (POCT) coagulometers are increasingly being used in the hospital setting. We investigated whether the prothrombin time international normalized ratio (INR) results by CoaguChek XS Plus (Roche Diagnostics GmbH, Mannheim, Germany) can be used reliably without being confirmed with the INR results by STA-R system (Diagnostica Stago S.A.S, Asnières sur Seine, France). Methods. A total of 118 INR measurements by CoaguChek XS Plus and STA-R were compared using Passing/Bablok regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…In our study, the correlation was also very strong when the CoaguChek XS Plus was compared with the photo‐optical (Sysmex CS‐2100i/CA‐1500) and the mechanical clot detection methods (Thrombolyzer XRC). Previous studies, that compared the CoaguChek XS Plus with photo‐optical (Sysmex analysers) or mechanical clot detection methods (STAGO analysers), found correlation coefficients approximately 0.95‐0.96; however, the CoaguChek XS Plus had never been compared before with different laboratory techniques simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the correlation was also very strong when the CoaguChek XS Plus was compared with the photo‐optical (Sysmex CS‐2100i/CA‐1500) and the mechanical clot detection methods (Thrombolyzer XRC). Previous studies, that compared the CoaguChek XS Plus with photo‐optical (Sysmex analysers) or mechanical clot detection methods (STAGO analysers), found correlation coefficients approximately 0.95‐0.96; however, the CoaguChek XS Plus had never been compared before with different laboratory techniques simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated an excellent correlation between photo‐optical and electromechanical coagulation analysers, while the comparison between POC and laboratory or manual INRs showed a certain variability in the results, with potential clinical disagreement and differences in VKA dosing . However, it is not known which test actually correlates better with the overall blood coagulation potential, because these three INR methods have never been compared simultaneously with global coagulation assays.…”
Section: Introductionmentioning
confidence: 99%
“…The blood was sent to the CUMC core laboratory for analysis, on a STA-R system (Diagnostica Stago S.A.S, Asnim, D sur Seine, France) using the STA-Neoplastine CI Plus kit. 12 This test uses a calcium thromboplastin reagent with an ISI of 1.32 to measure the clotting time of the patient's plasma and compares it with that of a normal standard. The test measures the activity of coagulation factors I, II, V, VII, and X as a whole.…”
Section: Core Laboratory Inr Testingmentioning
confidence: 99%
“…The international normalized ratio (INR) 4 derived from the prothrombin time is commonly used to monitor patients prescribed vitamin K antagonists like warfarin (1,2). Warfarin interferes with the synthesis of the vitamin K-dependent clotting factors II, VII, IX, and X as well as protein C and S (3).…”
mentioning
confidence: 99%
“…Traditional analytical performance studies of POCT INR devices assess device precision and accuracy relative to reference methods and evaluate the data with Bland-Altman plots, Passing-Bablok, or Deming regression analyses (4,5). In response to a recent post-market risk assessment of serious clinical and patient self-monitoring adverse events, the Food and Drug Administration (FDA) proposed more stringent performance expectations for POCT INR devices than those outlined in International Organization for Standardization (ISO) 17593:2007 or CLSI POCT14-A (6)(7)(8).…”
mentioning
confidence: 99%